The Medusa plot - Korman, Gordon (New York : Scholastic, 2011)
Thirteen-year-old Dan Cahill and his older sister, Amy, thought the search for the thirty-nine clues leading to the source of their family's power was over, but when Cahills are kidnapped by the Vespers, Amy and Dan find themselves with only a few day to fulfill a bizarre ransom request before their friends start dying.
Includes cards.
4.7
3-6
Keywords: Kidnapping -- Juvenile fiction; Orphans -- Juvenile fiction; Families -- Juvenile fiction; Cryptography -- Juvenile fiction; Genealogy -- Juvenile fiction; Kidnapping -- Fiction; Orphans -- Fiction; Family life -- Fiction; Cryptography -- Fiction; Genealogy -- Fiction; Mystery and detective stories; Kidnapping -- Fiction; Orphans -- Fiction; Family life -- Fiction; Cryptography -- Fiction; Genealogy -- Fiction; Mystery fiction; Code and cipher stories; Mystery fiction